In situ-crosslinked hydrogel-induced experimental glaucoma model with persistent ocular hypertension and neurodegeneration. (11th July 2022) - Lin, Jicheng; Xue, Jingfei; Xu, Qian; Liu, Zhe; Zhao, Chunyu; Tang, Jiahui; Han, Jiaxu; A, Sigen; Wang, Wenxin; Zhuo, Yehong; Li, Yiqing
Abstract : We designed an in situ -forming HB–PEG/HA–SH hydrogel suitable for intracameral injection and induced a persistent and stable ocular hypertension model. We integrated a standardized system of chronic ocular hypertension model evaluation. Abstract : A reliable animal model providing chronic and persistent ocular hypertension and characteristic neurodegeneration is essential to recapitulate human glaucoma and understand the underlying pathophysiological mechanisms behind this disease. Many approaches have been tried to establish persistently elevated intraocular pressure (IOP), while no efficient model and no systematic evaluation has been widely accepted yet. Herein, we developed a novel approach to reliably induce persistent IOP elevation using an injectable hydrogel formulated by hyperbranched macromolecular poly(ethylene glycol) (HB–PEG) and thiolated hyaluronic acid (HA–SH) under physiological conditions and established a systematic system for model evaluation. By formulation screening, an appropriate hydrogel with proper mechanical property, non-swelling profile and cytocompatibility was selected for further experiment. By intracameral injection, a persistent IOP elevation over 50% above baseline was obtained and it led to progressive retinal ganglion cell loss and ganglion cell complex thickness reduction. The evaluation of the efficacy of the model was thoroughly analyzed by whole-mounts retina immunostaining, optical coherence tomography, and hematoxylin–eosin staining for histological changes and by electroretinography for visual function changes. The N35–P50 amplitude of the pattern electroretinography and the N2–P2 amplitude of the flash visual-evoked potential were decreased, while the scotopic electroretinography showed no statistically significant changes. The in situ -forming HB–PEG/HA–SH hydrogel system could be an appropriate strategy for developing a reliable experimental glaucoma model without any confounding factors. We expect this model would be conducive to the development of neuroprotective and neuro-regenerative therapies.